An Analysis Of Types And Forms Of Code-Mixing In Indonesian Song Lyric By Saykoji - Vionita, Vionita; Shabri, Irsyad; Yanti, Rahma; Yalmiadi, Yalmiadi (LPPM Universitas Dharma Andalas, 2023)
The purpose of this study was to determine the type of code-mixing and the form of code-mixing of 8 song lyrics of Saykoji in the 2006 album. This study uses the code-mixing theory of Nababan, (1984). This research includes a qualitative description. This study used the Independent See-Engage-talk Technique (TSBLC) and Technique Direct Element (BUL) to analyze the data. This study focuses on the type of code-mixing using theory Suwito's (1983), and the form of code-mixing using theory Suwito's (1995). After conducting the analysis, there were sixty-six (66) data found in the code-mixing type and fifty-seven (57) data in the code-mixing form. According to Suwito, there are two types of code-mixing, namely Inner and Outer. After being analyzed, it was found that the Inner code-mixing in eight (8) Saykoji song lyrics was 15 (22.72%) while the outer code-mixing was found to be 51 (72.27%). The form of code mixing according to Suwito consists of six namely word, phrase, baster, repetition, idiom, and clause. After being analyzed, the highest percentage is word 32(56,14%), The second position is phrase 7(12, 2%), Idiom 6 (10, 52%), Clause 5(8,77%), repetition 4 (7 %), baster 3 (5.26%).